Impact of Education and Data Feedback on Antibiotic Prescribing for Urinary Tract Infections in the Emergency Department: An Interrupted Time-Series Analysis . (1st February 2022) - Nys, Cara L; Fischer, Kristen; Funaro, Jason; Shoff, Christopher J; Theophanous, Rebecca G; Staton, Catherine A; Mando-Vandrick, Jennifer; Toler, Rachel; Shroba, Jenny; Turner, Nicholas A; Liu, Beiyu; Lee, Hui Jie; et al.
Abstract: Background: Urinary tract infections (UTIs) are often misdiagnosed or treated with exceedingly broad-spectrum antibiotics, leading to negative downstream effects. We aimed to implement antimicrobial stewardship (AS) strategies targeting UTI prescribing in the emergency department (ED). Methods: We conducted a quasi-experimental prospective AS intervention outlining appropriate UTI diagnosis and management across 3 EDs, within an academic and 2 community hospitals, in North Carolina, United States. The study was divided into 3 phases: a baseline period and 2 intervention phases. Phase 1 included introduction of an ED-specific urine antibiogram and UTI guideline, education, and department-specific feedback on UTI diagnosis and antibiotic prescribing. Phase 2 included re-education and provider-specific feedback. Eligible patients included adults with an antibiotic prescription for UTI diagnosed in the ED from 13 November 2018 to 1 March 2021. Admitted patients were excluded. The primary outcome was guideline-concordant antibiotic use, assessed using an interrupted time-series regression analysis with 2-week intervals. Results: Overall, 8742 distinct patients with 10 426 patient encounters were included. Ninety-two percent of all encounters (n = 9583) were diagnosed with cystitis and 8.1% with pyelonephritis (n = 843). There was an initial 15% increase in guideline-concordant antibiotic prescribing in phase 1 compared with the preintervention period (incidence rate ratio [IRR], 1.15; 95% confidence interval [CI], 1.03–1.29). A significant increase in guideline-concordant prescriptions was seen with every 2-week interval during phase 2 (IRR, 1.03; 95% CI, 1.01–1.04). Conclusions: This multifaceted AS intervention involving a guideline, education, and provider-specific feedback increased guideline-concordant antibiotic choices for treat-and-release patients in the ED. Abstract : A multidisciplinary antimicrobial stewardship intervention utilizing treatment guidelines supported by local antibiogram data and literature, education, and data feedback increased guideline-concordant urinary tract infection antibiotic treatment choices across 3 emergency departments.